Current treatment of biliary Sphincter of Oddi Dysfunction - Zeng, Hong-Ze; Yi, Hang; He, Song; Wu, Rong; Ning, Bo (Frontiers in Medicine, 2024)
The sphincter of Oddi is a delicate neuromuscular structure located at the junction of the biliary-pancreatic system and the duodenum. Sphincter of Oddi Dysfunction (SOD) can result in various clinical manifestations, including biliary-type pain and recurrent idiopathic pancreatitis. The management of SOD has been challenging. With the publication of the landmark Evaluating Predictors and Interventions in Sphincter of Oddi Dysfunction (EPISOD) trial and the Rome IV consensus, our clinical practice in the treatment of SOD has changed significantly in recent years. Currently, the management of type II SOD remains controversial and there is a lack of non-invasive therapy options, particularly for patients not responding to endoscopic treatment. In this mini review, we aimed to discuss the current knowledge on the treatment of biliary SOD.